2012
DOI: 10.1152/jn.00315.2012
|View full text |Cite
|
Sign up to set email alerts
|

Structural learning in feedforward and feedback control

Abstract: Yousif N, Diedrichsen J. Structural learning in feedforward and feedback control. J Neurophysiol 108: 2373-2382, 2012. First published August 15, 2012 doi:10.1152/jn.00315.2012.-For smooth and efficient motor control, the brain needs to make fast corrections during the movement to resist possible perturbations. It also needs to adapt subsequent movements to improve future performance. It is important that both feedback corrections and feedforward adaptation need to be made based on noisy and often ambiguous se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 36 publications
13
62
0
Order By: Relevance
“…This finding is in line with a recent study by Yousif and Diedrichsen [16] showing that adaptive changes in feedback responses could be observed in both consistent and inconsistent environments, whereas changes in feedforward adaptation were only present in consistent environments. The positive relationship between environmental variability and feedback response strength is in line with several previous studies [1721] and consistent with the idea that the variance of an environment informs the variance of the prior for Bayesian integration [2225].…”
Section: Resultssupporting
confidence: 92%
“…This finding is in line with a recent study by Yousif and Diedrichsen [16] showing that adaptive changes in feedback responses could be observed in both consistent and inconsistent environments, whereas changes in feedforward adaptation were only present in consistent environments. The positive relationship between environmental variability and feedback response strength is in line with several previous studies [1721] and consistent with the idea that the variance of an environment informs the variance of the prior for Bayesian integration [2225].…”
Section: Resultssupporting
confidence: 92%
“…In separate studies, Magescas and colleagues and Yousif and Diedrichsen found that online corrections can arise with or without adaptation depending on the nature of perturbation, implying that these phenomena, and thus their underlying mechanisms, are dissociable [28,29]. Moreover, motor learning need not result from a forward model-based process at all; Huang and colleagues have shown that task success, independent of sensory error driven adaptation, can reshape motor output [30], supporting the existence of model-free approaches to motor learning [23,26].…”
Section: Forward Models For Forelimb Movementmentioning
confidence: 99%
“…If surgeons are able to learn general rules about how port properties vary this may alleviate the negative consequences associated with port switching. Experimental findings show that training regimes in which task parameters are randomly or gradually varied provide support for the extraction of structural rules [2,[7][8][9]. Even when the structural rules are not extracted, motor task variation can improve future performance through other mechanisms [10][11][12][13].…”
Section: Introductionmentioning
confidence: 97%